Pressure injury prevalence in Australian intensive care units: A secondary analysis. Issue 6 (November 2022) - Coyer, Fiona; Chaboyer, Wendy; Lin, Frances; Doubrovsky, Anna; Barakat-Johnson, Michelle; Brown, Wendy; Lakshmanan, Ramanathan; Leslie, Gavin; Jones, Sarah L.; Pearse, India; Martin, Kerrie; McInnes, Elizabeth; et al.
Abstract: Background: Pressure injuries (PIs) are an enduring problem for patients in the intensive care unit (ICU) because of their vulnerability and numerous risk factors. Method: This study reports Australian data as a subset of data from an international 1-day point prevalence study of ICU-acquired PI in adult patients. Patients aged 18 years or older and admitted to the ICU on the study day were included. The outcome measure was the identification of a PI by direct visual skin assessment on the study day. Data collected included demographic data and clinical risk factors, PI location and stage, and PI prevention strategies used. Descriptive statistics were used to describe PI characteristics, and odds ratios (ORs) were used to identify factors associated with the development of a PI. Results: Data were collected from 288 patients from 16 Australian ICUs. ICU-acquired PI prevalence was 9.7%, with 40 PIs identified on 28 patients. Most PIs were of stage 1 and stage 2 (26/40, 65.0%). Half of the ICU-acquired PIs were found on the head and face. The odds of developing an ICU-acquired PI increased significantly with renal replacement therapy (OR: 4.25, 95% confidence interval [CI]: 1.49–12.11), impaired mobility (OR: 3.13, 95% CI: 1.08–9.12), fastest respiratory rate (OR: 1.05 [per breath per minute], 95% CI: 1.00–1.10), longer stay in the ICU (OR: 1.04 [per day], 95% CI: 1.01–1.06), and mechanical ventilation on admission (OR: 0.36, CI: 0.14–0.91). Conclusion: This study found that Australian ICU-acquired PI prevalence was 9.7% and these PIs were associated with many risk factors. Targeted PI prevention strategies should be incorporated into routine prevention approaches to reduce the burden of PIs in the Australian adult ICU patient population.